(untitled) (Journal of Misan Researches, 2021)
The aim of the research is to identify (the effectiveness of an educational program based on the Schmeck model in achievement and deep understanding among students of the third intermediate class in mathematics). The sample consisted of (70) students of the third intermediate grade, by (34) students in the experimental group who studied mathematics in the program. Education based on Schmeck’s model, and (36) students in the control group who studied the same subject in the usual way, then statistically rewarded them in variables (chronological age, mathematics score for the previous school year, intelligence test, and previous mathematics test). He prepared an achievement test of (40) objective items, and a test for deep understanding of (30) objective items that were evenly divided into five skills, and both tests were of a multiple-choice type, and their psychometric properties were verified, and after the experiment was completed and the two tools applied, the results showed: The superiority of the group students Experimental on students of the control group in the two tests (achievement and deep understanding).